The President’s Expression: Analyzing the Psychological Aspects of Susilo Bambang Yudhoyono’s Lyrics - Adinugroho, Indro; Muhamad, Roby; Susianto, Harry (UI Scholars Hub, 2021)
Word and text analysis has become an alternative method to examine social and psychological problems when other common methods could not access the internal workings of a participant’s psyche. This study shows that text analysis, as an alternative method, is capable to identify important psychological aspects contained in the song lyrics written by Susilo Bambang Yudhoyono (SBY) with regard to his strategic role as a country and political leader. Three main aspects are identified: emotion, achievement, and harmony. The lyrics of 23 Indonesian songs written by SBY have been gathered for the purpose of analysis. Three studies were carried out to analyze the psychological aspects contained in SBY’s song lyrics. Firstly, the author applied algoritma kata (AK – word algorithm) to identify the degrees of valence and arousal in each song using the word count method. Secondly, the author applied analisis lirik keseluruhan (ALK – the whole lyric analysis) to assess the valence and arousal in every song by means of human judgment. Third, the author applied expert judgment (EJ) to analyze the dominant words that emerge in all song lyrics. This study shows that SBY’s song albums have consistently shown a positive valence and an increasing level of arousal from 2006 to 2014. In addition to that, EJ method shows that those dominant words represent SBY’s two most prominent psychological aspects: achievement and harmony.